A Descriptive Study of Teachers’ Pedagogical Competence Based on the Indonesian Madrasah Competency Assessment (AKMI) - Lutfi Rahman Purbasari; Anna Fitri Hindriyana; Agus Yadi Ismail (Postgraduate, University of Mataram, 2025)
The purpose of this study is to analyze how teachers’ pedagogical competence contributes to the implementation of the Indonesian Madrasah Competency Assessment (AKMI) program and its influence on students’ literacy performance. This research employs a descriptive–exploratory qualitative design using multiple case study sites in three districts: Kuningan, Majalengka, and Ciamis across the MI, MTs, and MA levels. Qualitative data were collected through in-depth interviews, observations, and document analysis, while quantitative data from teacher pedagogical competence questionnaires and student AKMI report cards were used as supporting materials to strengthen the interpretation of the qualitative findings. The results show that AKMI training (BIMTEK) has been implemented adequately, enabling teachers to apply literacy-based lesson planning and contextual learning strategies. Teachers reported gains in understanding differentiated learning and the use of AKMI reports, although several challenges remain—particularly limited conceptual mastery, insufficient dissemination, tight implementation schedules, and constraints in online training. The analysis also indicates a tendency that higher pedagogical competence is aligned with better student literacy outcomes, although the relationship is not yet strongly consistent across levels. In conclusion, pedagogical competence plays an essential role in supporting the effectiveness of AKMI implementation, yet continuous mentoring and strengthened conceptual training are required to optimize program outcomes.